Worsening psychosis associated with administrations of buspirone and concerns for intranasal administration: A case report - Apeldoorn, Samuel; Chavez, Rebecca; Haschemi, Freshta; Elsherif, Kareem; Weinstein, David; Torrico, Tyler (Frontiers in Psychiatry, 2023)
Buspirone is commonly used to treat generalized anxiety disorder and demonstrates a limited side-effect profile compared to other anxiolytics. Buspirone is considered generally safe, and neuropsychiatric adverse reactions are uncommon. There are rare clinical case reports that suggest buspirone-induced psychosis. We present a case of buspirone worsening psychosis for a patient psychiatrically hospitalized for an episode of decompensated schizoaffective disorder. The patient had a primary diagnosis of schizoaffective disorder and was treated with antipsychotics during this hospitalization, but his symptoms worsened when buspirone was administered on two separate occasions. During the first trial of buspirone, the patient exhibited traits of increased aggression, odd behaviors, and paranoia. The buspirone was discontinued after the patient admitted to hiding his pills to later consume through nasal ingestion. The second trial resulted in repeated exacerbated symptoms of paranoia related to food and substantially decreased oral intake. Considering its complex mechanism of action, buspirone is suggested to derive its neuropharmacological effects through 5-HT1A receptors. However, the drug also has been found to mediate dopamine neurotransmission. Buspirone acts as an antagonist at presynaptic dopamine D2, D3, and D4 receptors. Yet, contrary to expected outcomes, it was unable to produce antipsychotic effects and instead resulted in a substantial increase in dopaminergic metabolites. The route of administration may also play a role in the enhancement of the buspirone’s effects, particularly considering that after first-pass metabolism, buspirone has approximately 4% oral bioavailability. Intranasal administration of buspirone leads to faster drug absorption by direct transport from the nasal mucosa to the brain and increased bioavailability.